Pengembangan Bahan Ajar Matematika SMA dengan Model Creative Problem Solving Terintegrasi TPACK - Edy Waluyo (Jurnal Pendidikan Matematika : Judika Education, 2023)
The purpose of this study is to develop mathematics-based teaching materials with the TPACK integrated Creative Problem Solving model. The method used in this research is Borg & Gall model development research including needs analysis, product design, product development, product implementation and evaluation. The subjects of this study were class XII B and XI C students of SMAN 2 Selong totaling 70 students. The results showed that the teaching materials developed were included in the valid category according to material experts and linguists. Teaching materials are also classified as practical based on student responses after using teaching materials during learning. Teaching materials are classified as effective as indicated by t count = 23.71 > t table =1.66. In conclusion, the development of high school mathematics teaching materials with an integrated creative problem solving model TPACK can improve student learning outcomes on integral materials. Keywords: Creative Problem Solving, TPACK